Politeness Strategies Used by the Main Character in Spongebob Squarepants Movie - Ina Mutmainah; Akhmad Baihaqi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2018)
The objective of this research is to analyze the SpongeBob movie with the title SpongeBob Movie Sponge Out of Water Food Fight. It is to identify the politeness strategies applied by the main characters in SpongeBob Square Pants. The researcher uses qualitative research. The data was taken from Video movie in SpongeBob Movie Sponge Out of Water Food Fight. The result showed that Bald on record strategy is the most frequent strategy (14 out of 42 total data). It is followed by positive politeness strategy (12 out of 42), Off-Record strategy (8 out of 42) and Negative politeness (7 out of 42). This film prefers to apply bald-on record in conveying their utterances to the other, especially Mr. Crabs toward SpongeBob and Patrick as employee in his office. It concludes that there is a good relationship between SpongeBob and Patrick, SpongeBob and Mr. Krab, so the conversation used positive politeness.